Aggregate Safety Stock Levels and Component Part Commonality - Collier, David A. (Management Science, 1982)
The relationship between aggregate safety stock inventory levels and component part commonality is developed. A simulation experiment strongly supports the functional form of this relationship in an uncertain operating environment. Managers can use these equations to assess the trade-offs between aggregate safety stock levels, service level and the degree of component part standardization. For example, these relationships can be used to predict service, inventory level and cost standards for any change in component part commonality.